1993
DOI: 10.1021/bi00094a015
|View full text |Cite
|
Sign up to set email alerts
|

PACE4 is a member of the mammalian propeptidase family that has overlapping but not identical substrate specificity to PACE

Abstract: Proteins that transit the constitutive pathway of secretion frequently require proteolytic processing after a pair of basic amino acids to attain their full functional activity. A ubiquitously expressed calcium-dependent subtilisin-like serine protease, named PACE or furin, can cleave precursor polypeptides specifically at pairs of basic amino acids where an arginine residue is present in the P4 position. Another member of this protease family, PACE4, was cloned recently by a PCR-based strategy and was also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 26 publications
1
45
3
Order By: Relevance
“…The role that the furin homolog PACE4 may play in the liver is presently unclear but recent co-expression experiments have shown it to be proteolytically active and somewhat different to furin in its cleavage of mutated pro Von Willebrand factor (which is not produced in hepatocytes but endothelial cells). PACE4's lack of inhibition by g:antitrypsin Pittsburgh [20], however, makes it substantially different from furin and the in situ enzyme. The findings here, on the other hand, show that furin has a similar specificity to that expected of the in situ convertase.…”
Section: Discussionmentioning
confidence: 99%
“…The role that the furin homolog PACE4 may play in the liver is presently unclear but recent co-expression experiments have shown it to be proteolytically active and somewhat different to furin in its cleavage of mutated pro Von Willebrand factor (which is not produced in hepatocytes but endothelial cells). PACE4's lack of inhibition by g:antitrypsin Pittsburgh [20], however, makes it substantially different from furin and the in situ enzyme. The findings here, on the other hand, show that furin has a similar specificity to that expected of the in situ convertase.…”
Section: Discussionmentioning
confidence: 99%
“…However, no secretion of human PACE4 was detected from transfected COS-1 cells [32]. To investigate the synthesis and secretion of PACE4 more thoroughly, the hEK-293 line and additional stably transfected neuroendocrine and fibroblast cells were examined ( Figure 1).…”
Section: Biosynthesis Of Pace4 In Fibroblasts and Neuroendocrine Cellsmentioning
confidence: 99%
“…Since PACE4 is encoded on the same chromosome as furin, and since some early reports suggested that PACE4 was not secreted and had a wide tissue distribution, the latter has been regarded as a soluble intracellular version of furin [32,61]. However, a further examination of PACE4 is important for several reasons.…”
Section: Biosynthesis Intracellular Routing and Secretion Of Pace4mentioning
confidence: 99%
See 1 more Smart Citation
“…PACE4 was also demonstrated to have intracellular processing activity by cleaving pro-von Willebrand factor (Creemers et al, 1993;Rehemtulla et al, 1993). The catalytic domain of PACE4 exhibits 70% identity to that of PC5.…”
mentioning
confidence: 99%